Kalibrasi Sensor Tegangan dan Sensor Arus dengan Menerapkan Rumus Regresi Linear menggunakan Software Bascom AVR - Jumrianto, Jumrianto (Journal of System, Information Technology and Electronics Engineering, 2021)
Calibration is mandatory for each measuring device. The government has formed several institutions to handle the calibration of measuring devices. LIPI with Metrology Research Center, Ministry of Health with Health Facility Testing Center, Industry and Trade Service with Metrology Center. The calibration of voltage sensors and current sensors in this paper is done by taking a sample of data on a voltage sensor with a range of 0 - 220 volts and feeding it to a step up transformer with a range of 0-8000 volts. Current sensor range 0 - 5 amperes. The data were processed with Microsoft Excel to obtain the Linear Regression Formula and applied to the Bascom AVR Software and compared the results with a standard multimeter. The application of the Linear Regression Formula to the voltage sensor calibration in this paper, obtains the Mean Absolute Percentage Error of 3.21%, with a deviation of 113.98, and a measurement accuracy of 96.97%. While the application of the Linear Regression Formula on the ZMCT103C current sensor calibration, the Mean Absolute Percentage Error is 7.74%, with a deviation of 7.83 and a measurement accuracy of 92.26%.